Strength Analysis of Existing Upper Structure of Right Wing Building Jambi University Teaching Hospital - Nuklirullah, M.; Dwina, Dila Oktarise; Ofronazel, Ekom (Jurnal Fondasi, 2024)
The building of the Teaching Hospital at Jambi University has stopped until now with the current development of physical development in the form of the upper structure work stage of the building. To be able to resume the physical construction of the RSP UNJA building, it is necessary to have a technical study in the form of an evaluation of the building's current structural state, to ensure that the existing structure has good strength and is feasible to continue the stages of work until it is completed according to planning. The technical standards used by the planning consultant in its 2015 planning used old standards, while the standards used have been updated with the latest technical standards. Building planning data and existing data on completed work are gathered as part of the evaluation approach employed in this study, then an analysis is carried out based on the latest standards. The analysis's findings indicate that while all floor slab structure elements at every level satisfy the requirements for moment strength and shear force, some beam elements in specific locations do not, and all column types satisfy the requirements for axial strength but some column elements in specific locations do not meet the requirements for shear force strength. From the results of the analysis and conclusions, it was obtained that some of the existing structures meet the strength requirements which means that they can withstand the load of the working service.